Enhanced oxygen-release/storage properties of Pd-loaded Sr3Fe2O7−δ. Issue 21 (19th May 2017) - Beppu, Kosuke; Hosokawa, Saburo; Shibano, Takuya; Demizu, Akito; Kato, Kazuo; Wada, Kenji; Asakura, Hiroyuki; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : Pd metal nanoparticles highly dispersed on Sr3 Fe2 O7− δ dramatically enhance the release process of lattice oxygen under H2 atmosphere. Abstract : This study proves that a small amount of Pd loading (1 wt%) on Sr3 Fe2 O7− δ can dramatically enhance the oxygen-storage properties of Sr3 Fe2 O7− δ . The topotactic oxygen intake and release between Sr3 Fe2 O6.75 and Sr3 Fe2 O6 takes place in response to gas switching between an O2 flow and H2 flow, regardless of the presence or absence of Pd loading. The effect of Pd loading is significant for the oxygen-release process under H2 atmosphere; that is, highly dispersed Pd metal nanoparticles sized less than 1 nm formed on Pd/Sr3 Fe2 O7− δ to promote H2 dissociation, resulting in the improvement of the oxygen-release temperature and rate. Pd/Sr3 Fe2 O7− δ with a layered perovskite structure has a higher oxygen-release property at lower temperature than Pd/SrFeO3− δ with a perovskite phase without the layered structure. These facts indicate that the surface reaction as well as the crystal structure are responsible for the oxide ion mobility in perovskite structure, and also provide guidelines for designing novel oxygen-storage materials.